Математичні моделі термодинамічних процесів біологічного організму - Стенцель, Й. І.; Павлов, С. П.; Літвінов, К. А. (НТУ "ХПІ", 2014)
На основі результатів клінічних досліджень температурних змін здорової та хворої людини, принципів реологічних переходів кількості теплової енергії та методу нульового градієнта розроблені математичні моделі термодинамічних процесів біологічного організму. Показані причини зміни термодинамічного поля здорової та хворої людини. На амплітуду зміни температури чинить вплив температура організму та час кровообігу, а також витрата крові.

Based on the results of clinical studies of temperature changes healthy and sick man of principles rheological transitions of the heat energy and zero-gradient method the mathematical model of the thermodynamic processes of a biological organism. The following reasons for the change of the thermodynamic fields of healthy and sick person. The amplitude of temperature changes influencing factors such as the size of a normal body temperature and blood circulation time, and mass flow of blood in the circulatory system, as well as natural options. Theoretical foundations of heat transfer in a biological organism, provided that the latter is in a certain environment with ideal insulating properties. The heat that is emitted as a result of biochemical reactions in some part of the body, distributed by rheological transitions through the walls of blood vessels to blood flow and evenly spread throughout its volume. In this case assumed that the heat from its source (shocked region of the body) is stored in the volume of the circulatory system and is transmitted uniformly in time muscular and other parts of the body. The amplitude of daily temperature for a healthy body is practically constant and is determined by the degree of attenuation of the temperature field, which depends on the gradient of change of thermal energy, the volume flow of blood in the circulatory system, the current amount of thermal energy and volume of the circulatory system.
Mathematical models of thermodynamic processes of the biological organism
Keywords: біологічні організми; кровоносна система; захворювання; реологічний перехід; теплова енергія; температурне поле; biological organism; circulatory system; disease; thermal energy